The ultimate money guide for bubbles, busts, recession, and depression - Weiss, Martin D. (John Wiley & Sons, 2011)
"Updated version of the bestselling book on how to grow and protect wealth in difficult economic times Having an effective financial plan has always been important; today, it's crucial. In The Ultimate Money Guide for Bubbles, Busts, Recession, and Depression--the updated and revised edition of the bestseller, The Ultimate Depression Survival Guide--author Martin D. Weiss shows readers how to create a safe and effective financial plan for today's unpredictable economic environment. Explains why the U.S. economy continues to slump, and how persistently high unemployment and increasing government spending could lead to a far worse, double-dip recession. Details how investors are missing opportunities by failing to look at overseas investments, specifically in Asia and Latin America. Reveals what everyone should be doing now to protect their savings, investments, and jobs. The Ultimate Ultimate Money Guide for Bubbles, Busts, Recession, and Depression answers the questions readers have about the new challenges of the "new normal," while also offering strategies to cope with the credit crunch, housing bust, and decline of the U.S. dollar"